The synergistic effect of deuterium and helium on the microstructure evolution of W–Y2O3 material during plasma exposure - Meiye Pan; Lipeng Sun; Yifan Zhang; Jing Wang; Laima Luo; Yucheng Wu (Nuclear Fusion)
This study presents a systematic investigation of the synergistic effect of deuterium and helium on the microstructural evolution of W–Y _2 O _3 material during plasma exposure. The effect of single D/He and sequential D/He, He/D plasma exposure on the stability of Y _2 O _3 nanoparticles and the microstructural evolution of the W matrix were investigated using scanning electron microscopy and transmission electron microscopy. The results indicate that Y _2 O _3 particles undergo a significant size change during plasma exposure, and this process was significantly influenced by the synergistic effects of hydrogen and helium. The size evolution of Y _2 O _3 particles is controlled by three mechanisms: the etching-controlled process at the initial stage, followed by deposition-controlled process or mixed-controlled processes. Interestingly, the fuzz structure on the surface of Y _2 O _3 particles is proved to be W instead of Y _2 O _3 , which results from the deposition during plasma exposure. Significant synergistic effects of deuterium and helium were observed, in which the strong combination of H and He-vacancy composites suppressed the bubble formation and growth, leading to a different evolutionary dynamic.